PENGEMBANGAN PENILAIAN AUTENTIK - Ikhsan, Moh. Hayatul (Institut Agama Islam Ibrahimy Genteng Banyuwangi, 2017)
This authentic assessment is the most basic thing that is listed in the K13 to find out to what extent learners master the competencies already established. Authentic assessment is assessment directly, where the teacher graded it is actually needed by learners in daily life. Authentic assessment should also be based on what is done by learners. Therefore the teacher should constantly assess learners through their performance in the classroom. From the background above, at this writing will Peel on